Improvement on the XTP public key cryptosystem and communication protocol of provable security - WANG Ze-hui (Tongxin xuebao)
A new trace function was proposed,the XTP public key cryptosystem based on the 3-rd order LFSR se-quence（the so-called XTR3 system） was extended to the XTR4 system based on the 4-th order LFSR sequence.XTR4 key was shorter in length than that of the XTR3 system under the same security level.Based on the XTR4 cryptosystem,the key exchange protocol,communication protocol of provable security,and one-time-pad protocol were proposed,which could be employed in variant environments to assure the security,as well as to improve the calculation efficiency.